Fibrosis in Human Adipose Tissue: Composition, Distribution, and Link With Lipid Metabolism and Fat Mass Loss - Divoux, Adeline; Tordjman, Joan; Lacasa, Danièle; Veyrie, Nicolas; Hugol, Danielle; Aissat, Abdelhalim; Basdevant, Arnaud; Guerre-Millo, Michèle; Poitou, Christine; Zucker, Jean-Daniel; Bedossa, Pierre; Clément, Karine (Diabetes (New York, N.Y.), 2010)
Fibrosis is a newly appreciated hallmark of the pathological alteration of human white adipose tissue (WAT). We investigated the composition of subcutaneous (scWAT) and omental WAT (oWAT) fibrosis in obesity and its relationship with metabolic alterations and surgery-induced weight loss. Surgical biopsies for scWAT and oWAT were obtained in 65 obese (BMI 48.2 ± 0.8 kg/m(2)) and 9 lean subjects (BMI 22.8 ± 0.7 kg/m(2)). Obese subjects who were candidates for bariatric surgery were clinically characterized before, 3, 6, and 12 months after surgery, including fat mass evaluation by dual energy X-ray absorptiometry. WAT fibrosis was quantified and characterized using quantitative PCR, microscopic observation, and immunohistochemistry. Fibrosis amount, distribution and collagen types (I, III, and VI) present distinct characteristics in lean and obese subjects and with WAT depots localization (subcutaneous or omental). Obese subjects had more total fibrosis in oWAT and had more pericellular fibrosis around adipocytes than lean subjects in both depots. Macrophages and mastocytes were highly represented in fibrotic bundles in oWAT, whereas scWAT was more frequently characterized by hypocellular fibrosis. The oWAT fibrosis negatively correlated with omental adipocyte diameters (R = -0.30, P = 0.02), and with triglyceride levels (R = -0.42, P < 0.01), and positively with apoA1 (R = 0.25, P = 0.05). Importantly, scWAT fibrosis correlated negatively with fat mass loss measured at the three time points after surgery. Our data suggest differential clinical consequences of fibrosis in human WAT. In oWAT, fibrosis could contribute to limit adipocyte hypertrophy and is associated with a better lipid profile, whereas scWAT fibrosis may hamper fat mass loss induced by surgery.